Improvement of HADOOP Ecosystem and Their Pros and Cons in Big Data (International Journal of Engineering and Computer Science, 2017)
Big data plays a major role in all aspects of business and IT infrastructure. Today many organizations, Social Media Networking Sites, E-commerce, Educational institution, satellite communication, Aircrafts and others generate huge volume of data on a daily basis. This data is in the form of structured, semi-structured and unstructured. So this huge voluminous amount of data is coined as big data. These big data should be stored and processed in the effective manner. But, in the traditional distributed system this data cannot be effectively handled because of lack of resources. So the term Hadoop comes in to the picture. Hadoop stores and process the huge voluminous amount of data with their strong Hadoop ecosystem. It contains many modules for processing the data, storing the data, allocating the resources, Configuration Management, retrieving the data and for providing highly fault tolerance mechanism. In this paper it focuses on big data concepts, characteristics, real time examples of big data, Hadoop Modules and their pros and cons.